Reliability of breath-holding tests with potential for use in sports practice - František Lörinczi; Drahomíra Lörincziová; Marián Vanderka (Journal of Kinesiology and Exercise Sciences)
Background: Breathing is a crucial yet often overlooked phenomenon in sports practice. Simple, quick, cost-free, and equipment-free breath-holding tests allow for the assessment of chemosensitivity of athletes. The purpose of this study was to verify the reliability of two breath-holding tests: static breath-holding test (SBHT) and walking breath-holding test (WBHT).Materials and Methods: The study assessed acute (intra-rater; ICC2,1) and inter-day (inter-rater; ICC2,k) test reliability. The research sample consisted of 207 individuals (74 adult males (31.12 9.84 years), 41 adult females (32.41 9.66 years), 67 adolescent males (13.73 1.34 years), and 25 adolescent females (14.28 1.81 years). While adolescents performed only the SBHT, the majority of adults completed both tests. An intraclass correlation coefficient (ICC) was employed to determine test-retest reliability. Pearson correlation coefficient (r) was used to detect correlations between SBHT and WBHT.Results: In summary, the acute reliability of both SBHT and WBHT was significant (p<0.01) and excellent (ICC2,1 = 0.947 and 0.971, respectively). For SBHT, both acute and inter-day reliability were higher in adults compared to adolescents (ICC2,1 =0.947 vs. 0.892; ICC2,k = 0.908 vs. 0.852). The inter-day reliability of SBHT was significant (p<0.01) and good (ICC2,k = 0.895) (excellent for adults; ICC2,k = 0.908). The inter-day reliability of WBHT was significant (p<0.01) and excellent (ICC2,k = 0.953). A significant positive strong correlation was noted (r = 0.61; p<0.01) between SBHT and WBHT.Conclusions: Both SBHT and WBHT appear to be highly reliable breath-holding tests suitable for sports practice. Higher reliability was noted in groups of adults compared to adolescents. There is a significant correlation between SBHT and WBHT, which points to common determinants of the tests.